CIDADES MÉDIAS NO CERRADO BRASILEIRO: DESAFIOS PARA A CONSERVAÇÃO DA BIODIVERSIDADE (Terr@ Plural, 2019)
The Brazilian Cerrado is a biome that encompasses one of the greatest biodiversity on the planet. Despite the high biodiversity, the Cerrado is also one of the most threatened biomes in the world with 132 endangered flora species. Due to its flat relief and favorable climatic conditions to produce soybeans exerting enormous pressure on the natural ecosystems. In addition to the pressure exerted with the expansion of areas destined to the agricultural culture, the agricultural commodities and services demanded by the soybean as transport, fuel, agricultural inputs, and labor have made the Brazilian Cerrado a very favorable scenario for the urban expansion and emergence of medium-sized cities in the context of agribusiness. In this scenario, the urban environmental management of these cities emerges as a possibility for the conservation of biodiversity in the Cerrado, avoiding the disappearance of species threatened with extinction. Therefore, the present article aims to discuss the main challenges of urban environmental management of medium-sized cities in the Brazilian Cerrado focused on the conservation of biodiversity.